Subclinical Atherosclerosis Could Increase the Risk of Hearing Impairment in Males: A Community-Based Cross-Sectional Survey of the Kailuan Study - Ruan, Chunyu; Mao, Xiang; Chen, Shuohua; Wu, Shouling; Wang, Wei (Frontiers in Neuroscience, 2022)
Objective: Subclinical atherosclerosis is a known risk factor of hearing impairment (HI). Brachial ankle pulse wave velocity (baPWV) is a good indicator of muscular artery elasticity and could be a feasible method to screen for subclinical atherosclerosis. Our study aimed to elucidate the relationship between baPWV and HI, providing a feasible diagnostic indicator to predict HI. Methods: This cross-sectional study was based on the Kailuan cohort. All participants completed a standardized questionnaire and underwent physical examinations and laboratory assessments at recruitment. Since 2010, some participants received additional baPWV testing during follow-up visits, and some who were exposed to occupational hazards such as noise received a pure-tone average hearing threshold (PTA) test after 2014. Male subjects with a complete physical examination, baPWV, and PTA data were recruited for this study. Multivariate linear and multivariate logistic regression analyses were used to evaluate the relationship between baPWV and PTA or HI. Results: Among 11,141 subjects, the average PTA was 20.54±10.40 dB, and the detection rate of HI was 1,821/11,141 (16.3%). As the baPWV quartile increased, age, systolic blood pressure, diastolic blood pressure, body mass index, total cholesterol, high-density-lipoprotein cholesterol, fasting blood glucose, and proportions of subjects reporting smoking, alcohol consumption, hypertension, and diabetes increased significantly (P < 0.05 for trend). The odds of HI were higher in the fourth quartile group (adjusted odds ratio [aOR]: 1.33, 95% confidence interval [CI]: 1.10 to 1.62) than in the first quartile group. For every 100 m/s increase in baPWV, the PTA increased by 13 dB (95% CI: 4 to 23). When we divided the subjects into young or non-young subgroups based on a cut-off age of 45 years, the aOR of the fourth quartile group increased to 2.65 (95% CI: 1.68 to 4.19), and the PTA increment increased to 18 dB (95% CI: 10 to 27) for every 100 m/s increase in baPWV in the young subgroup. Conclusion: Our study revealed the quantitative relationship between baPWV and HI. Although the results are not universally consistent, they suggest that screening baPWV could be a feasible diagnostic indicator to predict HI.